L’apostolo Paolo: un esempio da imitare o un imprevisto da affrontare? La recezione della figura e dei testi di Paolo nei primi secoli cristiani - Girolami, Maurizio (Liber Annuus, 2016)
Abstract This contribution retraces the first stages of the reception of the figure and the writings of the Apostle Paul. Starting from the New Testament texts, we realize that Paul has provoked different reactions: some have lauded the apostle (Acts of the Apostles and the Pastoral Letters), others seem to have ignored his existence (Johannine literature), yet others contest with much controversy his letters, despite being considered normative (2 Peter). Such a variety of opinions continues through the 2nd century with the Marcionites and Gnostics who exalt Paul, apologists such as Justin who ignore him and still those who, like the author of the pseudoclementine letters, consider Paul an enemy of the faith. In the latin-speaking world, Paul will be considered an example to imitate and a source of theological inspiration especially towards the end of the 4th century. Special attention is given to Irenaeus, who tries to find a harmony between such diverse attitudes toward Paul. He transmits as a legacy not only texts and examples but also criteria for discerning what is authentically apostolic.